2018
DOI: 10.1016/j.micres.2018.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and regulation of AcrABR, a RND-type multidrug efflux system, in Agrobacterium tumefaciens C58

Abstract: Agrobacterium tumefaciens AcrR is the transcriptional repressor of the acrABR operon. The AcrAB efflux pump confers resistance to various toxic compounds, including antibiotics [ciprofloxacin (CIP), nalidixic acid (NAL), novobiocin (NOV) and tetracycline (TET)], a detergent [sodium dodecyl sulfate (SDS)] and a biocide [triclosan (TRI)]. The sequence to which AcrR specifically binds in the acrA promoter region was determined by EMSA and DNase I footprinting. The AcrR-DNA interaction was abolished by adding NAL,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 53 publications
2
8
0
Order By: Relevance
“…These findings complement an earlier report describing enhanced resistance to TCS due to overexpressed acrAB multidrug efflux pump [58]. It was recently suggested that TCS binds to the transcriptional repressor AcrR, causing conformational changes and preventing its binding to the efflux pump AcrA promoter in Agrobacterium tumefaciens [59].…”
Section: Membrane and Cytoskeletal Damagesupporting
confidence: 88%
“…These findings complement an earlier report describing enhanced resistance to TCS due to overexpressed acrAB multidrug efflux pump [58]. It was recently suggested that TCS binds to the transcriptional repressor AcrR, causing conformational changes and preventing its binding to the efflux pump AcrA promoter in Agrobacterium tumefaciens [59].…”
Section: Membrane and Cytoskeletal Damagesupporting
confidence: 88%
“…Resistance in Salmonella caused by increasing concentrations of triclosan is associated with an overexpression of the AcrAB efflux pump [23]. A possible mechanism was shown with Agrobacterium tumefaciens where triclosan abolishes the interaction between the transcriptional repressor of the acrABR operon (acrR) and the DNA to which acrR specifically binds in the acrA promoter region [55]. A correlation between a decreased triclosan susceptibility and multidrug-resistance was shown in 428 Salmonella enterica isolates.…”
Section: Triclosanmentioning
confidence: 99%
“…Further, A. radiobacter has been recently described to cause ocular infections, and it was identified in polymicrobial keratitis cases [ 338 ]. Although there is not much information about the intrinsic AR of these bacteria, the presence of RND efflux pumps in the genus Agrobacterium [ 339 , 340 ] suggests that these bacteria may present low susceptibility to different drugs. Further, the finding of an A. radiobacter clinical isolates carrying different antibiotic-inactivating enzymes [ 341 ] indicate that this microorganism may possess a wide set of AR determinants.…”
Section: Emerging Opportunistic Pathogens With Environmental Originmentioning
confidence: 99%